PENERAPAN PENDIDIKAN KARAKTER DALAM MENINGKATKAN PERILAKU KEAGAMAAN SISWA DI MADRASAH TSANAWIYAH AL-MUNAWWARAH KOTA JAMBI - Ali Amin; Badarussyamsi; Syamsul Huda (STKIP Subang, 2024)
This research aims to find out how character education is implemented at the Al-Munawwarah Tsanawiyah Madrasah, Jambi City, and how character education contributes to increasing students' religious values at the Al-Munawwarah Tsanawiyah Madrasah, Jambi City. The approach used in this research is a descriptive-qualitative approach. The data collection techniques used were observation, interviews, and documentation. The data was analyzed by reducing the data, explaining the data, and drawing conclusions. Checking the validity of the data uses data triangulation techniques. The results of this research show that the character education process at Madrasah Tsanawiyah Al-Munawwarah, Jambi City, is carried out by integrating or internalizing character values into the subject matter in the learning process, such as bringing out or affixing the values contained in the subject matter and making comparisons with events. similar events in students' lives, then reveal values through discussion and brainstorming. There are several religious values applied at Madrasah Tsanawiyah Al-Munawwarah Jambi City, including faith and piety, then gratitude, then applying the 5S of politeness and sincerity, and the last one is honesty, both in learning and everyday life. Character education at Madrasah Tsanawiyah Al-Munawwarah Jambi City has contributed quite a lot to improving students' religious behavior. This can be seen in students who have become more motivated and diligent in carrying out religious ubudiyah activities, for example, Dhuha prayers every morning and also midday prayers in congregation.